PENGARUH METODE EKSPERIMEN GUNUNG MELETUS TERHADAP PERKEMBANGAN MOTORIK HALUS DI RA AS SHAFFAH KOTA BENGKULU - Harlinda Yati; Asiyah; Khosi'in (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Fine motor development is a crucial aspect of early childhood education as it relates to the coordination of hands, fingers, and eyes that support learning activities. Observations at RA As Shaffah Bengkulu City revealed that some children aged 5–6 years still experienced difficulties in fine motor skills, such as cutting, pasting, and holding writing tools. This study aimed to examine the effect of the volcano experiment method on the fine motor development of early childhood learners. The research employed a quantitative approach using a quasi-experimental design with a One Group Pretest–Posttest Design. The participants were 10 children from Group B at RA As Shaffah Bengkulu City. Data were collected using fine motor development observation sheets and analyzed using the Paired Sample t-Test. The results indicated an improvement in the average fine motor score from 19.00 (48%) in the pretest to 28.00 (70%) in the posttest. Statistical analysis showed a significance value of < 0.05, indicating a significant difference between pretest and posttest results. Therefore, it can be concluded that the volcano experiment method has a significant effect on improving fine motor development in children aged 5–6 years at RA As Shaffah Bengkulu City.